Correlation between Chondromalacia Patella and Patellofemoral Factors in Middle-Age Population: A Clinical, Functional, and Radiological Analysis - Kaur, Rashmeet; Dahuja, Anshul; Kaur, Chandanpreet; Singh, Jagdeep; Singh, Paramdeep; Shyam, Radhe (Indian Journal of Radiology and Imaging, 2021)
Background Despite higher incidence of patellofemoral pain (PFP) and consequently morbidity, the understanding about PF factors leading to PF arthritis is way lacking.Material and Methods A prospective study of first 80 patients who were diagnosed with chondromalacia patella (CMP) on magnetic resonance imaging (MRI) divided into early and late CMP groups were evaluated clinically, radiologically, and in terms of functional outcome.Results : Quadriceps angle, Clark’s test, and Insall–Salvati ratio results were nonsignificant despite greater values were observed in late CMP group, whereas trochlear morphology results (sulcus angle: 153:138 degrees and sulcus depth 3.9:5.4 mm) and clinical scores were significant in late CMP group (Kujala’s score: 61:78, whereas PF pain score: 43:25). Type-C patellar morphology was found in greater number in late CMP cohort.Conclusion Trochlear and patellar morphologies along with clinical scores play a key role in understanding of the CMP.
Keywords: chondromalacia patella; patellofemoral; trochlea